Analisis Disparitas Garis Kemiskinan Di Kabupaten Bone Bolango (Studi Kasus Kecamatan Kabila dan Kecamatan Bone Pantai) - Hamzah, Ilham; Canon, Syarwani; Santoso, Ivan Rahmat (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
Differences in economic conditions are one of the causes of income disparity in the community that triggers poverty in several regions. This study aims to determine whether there is an effect of differences in food and non-food commodity prices between Kabila District and Bone beach District. The research used a qualitative approach with descriptive methods. The sample in this study were 30 people. Data collection using observation, interviews and documentation. Data analysis techniques use reduction, data presentation, and conclusion drawing or verification. The results showed that the disparity in the poverty line in Kabila and Bone Pantai sub-districts was caused by price differences between food and non-food commodities which were influenced by several factors 1) Infrastructure, the infrastructure in Kabila sub-district is fairly adequate with fairly high operational costs compared to Bone Pantai sub-district with inadequate market conditions which utilise more roads around the market; 2) Distance, the distance between traders that occurs between regions through the place of production of finished goods in the kabila sub-district is more strategic than the Bone Pantai sub-district, but it is different in terms of natural resource supply where the Bone Pantai sub-district is more strategic in producing supplies of natural resources that are daily needs; 3) Transport Costs, high transport costs, then product prices tend to be higher in locations further from the source of production.